1992
DOI: 10.1056/nejm199203123261104
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Origin of Bladder Cancer

Abstract: A number of bladder tumors can arise from the uncontrolled spread of a single transformed cell. These tumors can then grow independently with variable subsequent genetic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
221
1
7

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(248 citation statements)
references
References 25 publications
19
221
1
7
Order By: Relevance
“…A wealth of evidence supports the concept that viral induced mammary tumors and hyperplasias in mice are clonal dominant populations and probably represent the progeny of a single cell (Cardi et al, 1983;Cohen et al, 1979a,b;Kordon et al, 1995;Young et al, 1971). Similar conclusions about monoclonality have been reached for human breast cancer, carcinoma of the colon, uterine, cervix and bladder, ovarian teratomas and many hematological neoplasms (Fearon et al, 1987, Sidransky et al, 1992, Wainscoat et al, 1990. This implies that mammary tumors and hyperplasias are developed from tissue-speci®c epithelial stem cells and therefore represent populations of mutated stem cells and their di erentiating progeny.…”
Section: Introductionmentioning
confidence: 74%
“…A wealth of evidence supports the concept that viral induced mammary tumors and hyperplasias in mice are clonal dominant populations and probably represent the progeny of a single cell (Cardi et al, 1983;Cohen et al, 1979a,b;Kordon et al, 1995;Young et al, 1971). Similar conclusions about monoclonality have been reached for human breast cancer, carcinoma of the colon, uterine, cervix and bladder, ovarian teratomas and many hematological neoplasms (Fearon et al, 1987, Sidransky et al, 1992, Wainscoat et al, 1990. This implies that mammary tumors and hyperplasias are developed from tissue-speci®c epithelial stem cells and therefore represent populations of mutated stem cells and their di erentiating progeny.…”
Section: Introductionmentioning
confidence: 74%
“…In this study, two cases were immunohistochemically positive and SSCP negative (6% of the tumors). If the proportion of cells containing the mutation is low or if mutations occur outside the regions examined (exons 5 to 8), this could explain cases in which immunohistochemistry was positive but no mutation was detected (8,38). Conversely, six cases were immunohistochemically negative and SSCP positive (19%).…”
Section: Discussionmentioning
confidence: 99%
“…In the upper aerodigestive tract (3,4), lung (5), stomach (6), and liver (7), multiple carcinomas have been alleged to be multicentric in origin. Conversely, investigators have claimed that multiple tumors in the bladder (8,9), gynecologic organs (10 -12), and breast (13) have the same clonal origin rather than multicentric. Moreover, some investigators have reported that multiple tumors in the urothelial organs and liver can have either a common or an independent origin (14 -16).…”
mentioning
confidence: 99%
“…Molecular genetic studies support the monoclonality theory and indicate that tumour cells spread to multiple sites by intraepithelial or intraluminal seeding (Sidransky et al, 1992;Habuchi et al, 1993;Takahashi et al, 1998;Dalbagni et al, 2001), while other studies have shown that field effect underlies some multifocal urothelial tumours (Paiss et al, 2002;Jones et al, 2005). An understanding of the mechanism leading to accumulation of genetic alterations during multifocal tumour development may provide new prospects for both the early detection and prevention of the recurrence of urothelial cancer.…”
mentioning
confidence: 96%